FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI DALAM MENJUAL LADA HITAM DI DESA KARET JAYA KECAMATAN BUAY PEMACA KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This study aims to analyze the factors that influence the decision of farmers to conduct sales delay ordirectly selling black pepper in the village Karet Jaya district,Buay Pemaca subdistrict ogan Komering Ulu Selatan. This research was conducted subdiskrict buay pemaca in December 2016. The method used in this study is a survey method using a questionnaire while the sampling method is random layered unbalanced. The results showed that the factors that influence farmers' decision to sell black pepper are education, price, production, land area, and storage area. Binary logistic analysis results show that education, production, price, land area, and storage area significantly influences below 0.05.